Rethinking Development in Africa (Journal of Decolonising Disciplines, 2021)
In an intertextual assessment of Jacob’s Ladder (1987) and The Resolutionaries (2013), we are conducting a post-colonial analysis with the aim of showing that the post-colonization systems of sociopolitical and economic organization in African countries has no other objective but spoliation and subjugation of African economies to Western countries. For these two writers, and especially Armah, the international meetings which often gather the great leaders of this world in Africa and elsewhere are only “bloody ritual” meetings organized to make sure that the system of pillage is working perfectly. In this work, our objective is to show how Williams and Armah make use of the power of the imaginary to open the way to development in Africa, specifically by shaping a new African leadership which is ready to challenge the devil plan of Western hegemonic powers with as defiant programs as Fasseke’s nuclear project in Jacob’s Ladder (1987) and Nefert’s plan of unified linguistic construction in The Resolutionaries (2013).
Keywords: Independence; Colonialism; development; spoliation; conferences